No association between thickening fraction of the diaphragm and extubation success in ventilated children - Duyndam, Anita; Smit, Joke; Houmes, Robert Jan; Heunks, Leo; Molinger, Jeroen; IJland, Marloes; van Rosmalen, Joost; van Dijk, Monique; Tibboel, Dick; Ista, Erwin (Frontiers in Pediatrics, 2023)
Abstract Introduction In mechanically ventilated adults, thickening fraction of diaphragm (dTF) measured by ultrasound is used to predict extubation success. Whether dTF can also predict extubation success in children is unclear. Aim To investigate the association between dTF and extubation success in children. Second, to assess diaphragm thickness during ventilation and the correlation between dTF, diaphragm thickness (Tdi), age and body surface. Method Prospective observational cohort study in children aged 0-18 years old with expected invasive ventilation for >48 hours. Ultrasound was performed on day 1 after intubation (baseline), day 4, day 7, day 10, at pre-extubation, and within 24 hours after extubation. Primary outcome was the association between dTF pre-extubation and extubation success. Secondary outcome measures were Tdi end-inspiratory and Tdi end-expiratory and atrophy defined as < 10% decrease of Tdi end-expiratory versus baseline at pre-extubation. Correlations were calculated with Spearman correlation coefficients. Intra-rater and inter-rater reliability were calculated with intraclass correlation (ICC). Results Fifty-three patients, with median age 3.0 months (IQR 0.1-66.0) and median duration of invasive ventilation of 114.0 hours (IQR 55.5 - 193.5), were enrolled. Median dTF before extubation with Pressure Support 10 above 5 cmH2O was 15.2% (IQR 9.7-19.3). Extubation failure occurred in six children, three of whom were re-intubated and three then received non-invasive ventilation. There was no significant association between dTF and extubation success; OR 0.33 (95% CI; 0.06-1.86). Diaphragmatic atrophy was observed in 17/53 cases, in three of extubation failure occurred. Children in the extubation failure group were younger: 2.0 months (IQR 0.81-183.0) vs 3.0 months (IQR 0.10-48.0); p=0.045. At baseline, pre-extubation and post-extubation there was no significant correlation between age and BSA on the one hand and dTF, Tdi- insp and Tdi-exp on the other hand. The ICC representing the level of inter-rater reliability between the two examiners performing the ultrasounds was 0.994 (95% CI 0.970- 0.999). The ICC of the inter-rater reliability between the raters in 36 paired assessments was 0.983 (95% CI 0.974-0.990) Conclusion There was no significant association between thickening fraction of the diaphragm and extubation success in ventilated children